2014
DOI: 10.1007/s13277-014-1816-1
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12-CXCR4 axis promotes the natural selection of breast cancer cell metastasis

Abstract: CXCR4 and its ligand CXCL12 can promote the proliferation, survival, and invasion of cancer cells. They have been shown to play an important role in regulating metastasis of breast cancer to specific organs. High CXCR4 expression was also correlated to poor clinical outcome. Previous study also showed that tumor cells express a high level of CXCR4 and that tumor metastasis target tissues (lung, liver, and bone) express high levels of the ligand CXCL12, allowing tumor cells to directionally migrate to target or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 35 publications
2
81
1
2
Order By: Relevance
“…Effective targeting of fReANCs was determined by cellular association of AMD3100 functionalized probes using three breast cancer cell lines with varying levels of CXCR4 expression: 1) 4175‐TR (a highly aggressive, lung‐tropic subpopulation of the MDA‐MB‐231 cancer cell line with low CXCR4 expression, 2) MDA‐MB‐231, with moderate levels of CXCR4 expression, and 3) MCF‐7, with relatively high levels of CXCR4 expression . We observed a threefold increase in cellular association of fReANCs when compared to ReANCs by both receptor positive cell lines as determined by flow cytometry, with no significant change in association with receptor negative 4175‐TR cells (Figure 2 (Supporting Information) and Figure A,B,E).…”
Section: Resultsmentioning
confidence: 83%
“…Effective targeting of fReANCs was determined by cellular association of AMD3100 functionalized probes using three breast cancer cell lines with varying levels of CXCR4 expression: 1) 4175‐TR (a highly aggressive, lung‐tropic subpopulation of the MDA‐MB‐231 cancer cell line with low CXCR4 expression, 2) MDA‐MB‐231, with moderate levels of CXCR4 expression, and 3) MCF‐7, with relatively high levels of CXCR4 expression . We observed a threefold increase in cellular association of fReANCs when compared to ReANCs by both receptor positive cell lines as determined by flow cytometry, with no significant change in association with receptor negative 4175‐TR cells (Figure 2 (Supporting Information) and Figure A,B,E).…”
Section: Resultsmentioning
confidence: 83%
“…CXCR7 has been demonstrated to regulate cell migration and survival through several pathways that include ligand scavenging, direct signal transduction and direct interaction with CXCR45 . CXCR4 activation promotes tumour growth and metastasis in cancer, and recent preclinical studies have shown similar effects for CXCR7 . Agents blocking chemokine signalling by binding to these receptors are currently being developed for cancer therapy (eg ClinicalTrials.gov identifier NCT02179970, NCT02737072), supporting an evaluation of their efficacy in endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research reported that the expression of SDF-1 was elevated significantly in various carcinomas associated with tumor grade, lymph node metastasis, TNM stage and prognosis (11)(12)(13) with constitutive SDF-1 secretion, such as liver, lung, lymph nodes, and bone marrow, are also the most common sites for secondary metastasis of breast cancer (14)(15)(16). On the contrary, as a potent leukocytic chemokines, CXCL12 also has a potential to promote anticancer immunity by inducing CD8 + T cell activity, enhancing cytotoxicity, increasing the number of CD11c + cells in the tumor-draining lymph nodes and reducing the accumulation of myeloid-derived suppressor cells in the spleen (17).…”
Section: Introductionmentioning
confidence: 99%